The Effectiveness of Peaceful Education Learning Strategies for Students at Emergency Madrasas Following Natural Disasters in Sidoarjo - Abd Rachman Assegaf; Hani Khaulasari; Muhammad Thohir; Amjad Ali; Ratna Pangastuti (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This research aims to develop and evaluate learning strategies and curricula focused on risk management education for emergency schools in post-disaster areas. The goal is to support a peaceful learning process that helps students recover from trauma while improving motivation, academic performance, and disaster preparedness. Methods – This research uses the Borg & Gall Research and Development Model to find an appropriate instructional strategy for peace education in post-natural disaster school areas. Data collection was found through documentation, interviews, and observation. Field tests I, II, and III were conducted at Madrasa Ibtidaiyah (Islamic Elementary School) in Sidoarjo, which is close to the mud-flood areas of Lapindo Enterprise. Findings – The results show an improvement in test scores conducted over three cycles in class 3 ICP 1 and ICP 2. Additionally, students were enthusiastic about participating in the learning series. The research was concluded after cycle III as it was deemed effective. The strategy using disaster mitigation questions was effectively implemented in the science class (IPA) of ICP 1, contributing 56.9%, and in the religious class (akidah akhlak) of ICP 2, contributing 75.4%, enhancing student achievement, motivation, awareness, and readiness in disaster mitigation. The peaceful education strategy for disaster mitigation was more effectively applied in akidah akhlak classes. The validation criteria were sufficiently valid and proven effective for emergency madrasa students. Research implications/limitations – This studys implications have proven to be practically useful in handling post-disaster emergency education in madrasa environments in Sidoarjo through the instillation of peaceful education in the learning process of science and Islamic Religious Education. However, this study has limitations regarding the level and number of madrasas studied. Originality/value – The originality of this research is shown from the results of field findings in madrasa in Sidoarjo, with the validity value of the R&D Model Borg and Gall research method. Further research development can be done by expanding the types and levels of madrasas or schools in East Java.